Effect of Aqueous and Alcoholic Licorice (Glycyrrhiza Glabra) Root Extract Against Streptococcus Mutans and Lactobacillus Acidophilus in Comparison to Chlorhexidine: An In Vitro Study - Ajagannanavar, Sunil Lingaraj (Dentmedpub Research and Printing Co, 2014)
BACKGROUND: Glycyrrhiza (licorice) an herb, which has medicinal value and was used in ancient times as a remedy for a great diversity of ailments and sweetener. Roots of Glycyrrhiza contain a high concentration of saponin and glycyrrhizin, which are supposed to be sweetening agents. The aim of the study was to compare the efficacy of aqueous and alcoholic licorice root extract against Streptococcus mutans and Lactobacillus acidophilus in comparison to chlorhexidine (CHX). MATERIALS AND METHODS: In the first part of the study, various concentrations of aqueous and ethanolic licorice extract were prepared in the laboratory of Pharmacy College. It was then subjected to microbiological assay to determine its zone of inhibition using agar disk diffusion test and minimum inhibitory concentration (MIC) using serial broth dilution method against S. mutans and L. acidophilus. CHX was used as a positive control. RESULTS: MIC of aqueous and ethnolic licorice root extract against S. mutans and L. acidophilus were 25% and 12.5%, respectively. Mean zone of inhibition of the aqueous and alcoholic licorice extracts against S. mutans at 48 h were 22.8 mm and 26.7 mm, respectively. Mean zone of inhibition of the aqueous and alcoholic licorice extracts against L. acidophilus at 48 h were 14.4 mm and 15.1 mm, respectively. Mean zone of inhibition of the CHX against S. mutans and L. acidophilus at 48 h was 20.5 and 13.2, respectively. CONCLUSION: The inhibitory effect shown by alcoholic licorice root extract against S. mutans and L. acidophilus was superior when compared with that of aqueous form and CHX.